Is there a difference between Parkinson disease patients and a control group in terms of urinary symptoms and quality of life? - Benli, Erdal; Özer, Fahriye Feriha; Kaya, Yasemin; Özcan, Tuba Şaziye; Ayyıldız, Ali (Tubitak Scientific & Technical Research Council Turkey, 2016)
Background/aim: The aim of this study is to research whether urinary symptoms and disruption of quality of life observed in Parkinson disease patients are different than those of their healthy peers. Additionally, whether these complaints were affected by characteristics such as age at onset of Parkinson disease, sex, disease duration, and severity was investigated. Materials and methods: This study comprised a total of 79 individuals, 39 Parkinson patients and a control group of 40 individuals. Parkinson diagnosis was provided by a neurology expert according to the UK Parkinson's Disease Society Brain Bank Criteria. All patients were evaluated by a urologist with the International Prostate Symptom Score (IPSS) and an overactive bladder (OAB) questionnaire. Results: Compared with the control group, the Parkinson patient group had statistically significantly higher rates of urological complaints (P < 0.001), irritative symptoms (P < 0.001), voiding symptoms (P < 0.001), OAB score (P < 0.001), IPSS total score (P = 0.007), and treatment requirements (P < 0.001). Conclusion: Urologic complaints were observed more frequently in the Parkinson patient group compared to the control group. Another important result of this study is that in the Parkinson patient group there was no difference found between urologic complaints in terms of sex.
WOS: 000393331000009
PubMed ID: 28081354
Keywords: Parkinson Disease; Bladder Dysfunction; Lower Urinary Tract Symptoms